Dissolution equilibrium of Bi vapor and activities of Bi in liquid Ni-Cr-Fe-Nb solutions. (October 2018) - Xiaoliang, Li; Yaqian, Yang; Bo, Chen; Weiwei, Xing; Xu, Li; Kui, Liu
Abstract: The vapor pressure and the activity coefficients of minor elements at infinite dilution in liquid Ni-Cr-Fe-Nb alloys are a necessary and important basic property that is required to analyze the behavior of trace elements during metallurgical production process. The carrier gas method has been applied in this study of the dissolution equilibrium of Bi vapor pressures over liquid Ni-Cr-Fe-Nb alloys from 1723 K to 1823K and then the activities as well as the activity coefficients of Bi in liquid Ni-Cr-Fe-Nb alloys were calculated from the results. It is found that Bi shows strong negative deviation from Henry's Law, and the relationship between the standard free energy of dissolution reaction Bi(g) = [Bi]Ni-Cr-Fe-Nb and temperature is Δ G 0 = A + B T, where A is −163058 J/mol and B is 52.6 J/(mol⋅K). At 1773 K and 1873K, the activity coefficients γ of bismuth at infinite dilution is 0.442 and 0.253, respectively. Under the condition of conventional vacuum melting, the volatile lower limit of Bi can be up to 0.22 ppm, which was calculated by using thermodynamic data mentioned above. Highlights: The limit of Bi content in liquid Ni-Cr-Fe-Nb alloy at different temperatures and pressures was analyzed. It is found that Bi shows strong negative deviation from Henry's Law in the liquid Ni-Cr-Fe-Nb alloys. Derived properties considered include vapor pressure, Gibbs free energy and activity. High temperature and high vacuum are favorable for the volatilization of Bi in Ni-Cr-Fe-Nb alloys.